Onion yield as a function of nitrogen dose - Rodrigues,Gardênia S. de O. (2018)
Nitrogen (N) is the second most required nutrient by onion (Allium cepa L.); however, crop response to N fertilization depends on the applied dose. This study aimed to evaluate the effects of different N doses on onion bulb yield. The experiments were conducted during the period December 2011 to April 2012, with a second from August to December 2012, in a randomized block design with four replications. The treatments were six N doses: 0, 34, 67, 101, 134 and 168 kg ha-1. It may be concluded that the productive components of the onion were affected by N fertilization. The application of 67 kg ha-1 N, regardless of planting time, provided the maximum economic return for the onion crop.